The effects of Nigella sativa hydro-alcoholic extract and thymoquinone on lipopolysaccharide - induced depression like behavior in rats - Mahmoud Hosseini; Samaneh Zakeri; Sadieh Khoshdast; Fatemeh T Yousefian; Monireh Rastegar; Farzaneh Vafaee; Shamsi Kahdouee; Fatemeh Ghorbani; Hassan Rakhshandeh; S Abolfazl Kazemi (Wolters Kluwer Medknow Publications, 2012)
Background: Neuroimmune factors have been proposed as contributors to the pathogenesis of depression. Beside other therapeutic effects including neuroprotective, antioxidant, anticonvulsant and analgesic effects, Nigella sativa and its main ingredient, thymoquinone (TQ), have been shown to have anti-inflammatory effects. In the present study, the effects of Nigella sativa hydro-alcoholic extract and thymoquinone was investigated on lipopolysaccharide- induced depression like behavior in rats. Materials and Methods: 50 male Wistar rats were divided into 5 groups: Group 1 (control group) received saline instead of NS extract, thymoquinone or lipopolysaccharide. The animals in group 2 (lipopolysaccharide (LPS)) were treated by saline instead of NS extract and were injected LPS (100μg/kg, ip) 2 hours before conducting each forced swimming test. Groups 3 (LPS + NS 200) and 4 (LPS + NS 400) were treated by 200 and 400 mg/kg of NS (ip), respectively, from the day before starting the experiments and before each forced swimming test. These animals were also injected LPS 2hours before conducting each swimming test. The animals in group 5 received TQ instead of NS extract. Forced swimming test was performed 3 times for all groups (in alternative days), and immobility time was recorded. Finally, the animals were placed in an open- field apparatus, and the crossing number on peripheral and central areas was observed. Results: The immobility time in the LPS group was higher than that in the control group in all 3 times (P<0.001). The animals in LPS + NS 200, LPS + NS 400 and LPS + TQ had lower immobility times in comparison with LPS groups (P<0.01, and P<0.01). In the open- field test, the crossing number of peripheral in the LPS group was higher than that of the control one (P<0.01) while the animals of LPS + NS 200, LPS + NS 400 and LPS + TQ groups had lower crossing number of peripheral compared with the LPS group (P <0.05, and P<0.001). Furthermore, in the LPS group, the central crossing number was lower than that of the control group (P<0.01). In the animals treated by NS or TQ, the central crossing number was higher than that of the LPS group (P<0.05, and P<0.001). Conclusions: The results of the present study showed that hydro-alcoholic extract of Nigella sativa can prevent LPS-induced depression like behavior in rats. These results support the traditional belief on the beneficial effects of Nigella sativa in the nervous system. Moreover, further investigations are required in order to better understand this protective effect.